Methicillin-resistant Staphylococcus pseudintermedius synthesizes deoxyadenosine to cause persistent infection. Issue 1 (31st December 2021) - Bünsow, Dorothea; Tantawy, Eshraq; Ostermeier, Tjorven; Bähre, Heike; Garbe, Annette; Larsen, Jesper; Winstel, Volker
ABSTRACT: Methicillin-resistant Staphylococcus pseudintermedius (MRSP) is an emerging zoonotic pathogen of canine origin that causes an array of fatal diseases, including bacteremia and endocarditis. Despite large-scale genome sequencing projects have gained substantial insights into the genomic landscape of MRSP, current knowledge on virulence determinants that contribute to S. pseudintermedius pathogenesis during human or canine infection is very limited. Using a panel of genetically engineered MRSP variants and a mouse abscess model, we here identified the major secreted nuclease of S. pseudintermedius designated NucB and adenosine synthase A (AdsA) as two synergistically acting enzymes required for MRSP pathogenesis. Similar to Staphylococcus aureus, S. pseudintermedius requires nuclease secretion along with the activity of AdsA to degrade mammalian DNA for subsequent biosynthesis of cytotoxic deoxyadenosine. In this manner, S. pseudintermedius selectively kills macrophages during abscess formation thereby antagonizing crucial host immune cell responses. Ultimately, bioinformatics analyses revealed that NucB and AdsA are widespread in the global S. pseudintermedius population. Together, these data suggest that S. pseudintermedius deploys the canonical Nuc/AdsA pathway to persist during invasive disease and may aid in the development of new therapeutic strategies to combat infections caused by MRSP.